2017
DOI: 10.1111/gfs.12345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compaction, delayed sealing and aerobic exposure on forage choice and short‐term intake of maize silage by goats

Abstract: Forage choice and intake by ruminants depend on various factors. This study aimed to determine the effects of compaction, delayed sealing and aerobic exposure on forage choice and short‐term dry‐matter intake (DMI) of maize silage by goats. Whole‐crop maize (277 g/kg dry matter [DM]) in 120‐L silos was compacted at either low (194 kg DM/m3) or high (234 kg DM/m3) density, and sealed immediately at day 0 or with a delay at day 2 or day 4 post‐filling, making a total of six treatments. After ensiling for at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
(76 reference statements)
2
7
0
Order By: Relevance
“…Wichert et al (1998) reported that the silage exposed to air led to a decrease of roughage intake of cows. These reports (Brüning et al, 2018;Gerlach et al, 2013;Wichert et al, 1998) showed that silage with aerobic exposure reduces the DMI in ruminants, as is shown in our data.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Wichert et al (1998) reported that the silage exposed to air led to a decrease of roughage intake of cows. These reports (Brüning et al, 2018;Gerlach et al, 2013;Wichert et al, 1998) showed that silage with aerobic exposure reduces the DMI in ruminants, as is shown in our data.…”
Section: Discussionsupporting
confidence: 90%
“…The PMR intake of the low group tended to be lower than that of the high group. Brüning et al (2018) showed that aerobic exposure of maize silage caused strong avoidance and low DMI of goats. Gerlach et al (2013) demonstrated that strong changes concerning the fermentation products of maize silage during aerobic deterioration and decreased DMI of goats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2011) observed DM increase of 6.09% with longer exposure (305 vs. 324 g/kg). During the silage exposure process, evaporation of volatile organic compounds and moisture occurs, which can increase the DM content (Brüning et al., 2017). In addition, the second silage compaction during re‐ensiling can increase effluent loss and increase DM content, especially in silages with high moisture content (Michel et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, ensiled forage offered to ruminants has often resulted in a lower voluntary DMI compared with fresh (Donaldson and Edwards, 1976) or dried feed (Thiago et al, 1992). Various attempts have been made to establish relationships between silage composition and feed intake (e.g., Huhtanen et al, 2002Huhtanen et al, , 2007 as well as feed preference, including volatile fatty acids, alcohols, acetone, NH 3 -N, ethyl esters (Gerlach et al, 2013(Gerlach et al, , 2019Brüning et al, 2018), and biogenic amines (Scherer et al, 2019). These studies are valuable for the exploration of the relationships between the variety of nutrients and sensory properties of silages and forage choice of ruminants.…”
Section: Introductionmentioning
confidence: 99%